Perbedaan Keterampilan Komunikasi Melalui Model Pembelajaran Kooperatif Tipe Pair Check Dengan Berkirim Salam Dan Soal - Vella Anggresta; Rendika Vhalery (Universitas Negeri Padang, 2021)
The changes of curriculum affect all learning aspects including students. It changes the students’ communication skill, and it can be a problem. To overcome that problem, cooperative learning model is considered to be a solution because this model has many types of strategies such as think pair share (TPS) and send greetings and questions (SGQ). The aims of this study were to investigate the effect of TPS and SGQ implementation toward students’ communicative skills, and to find out the differences of students’ communication skill after learning through TPS and SGQ. This study was a comparative and experimental research. The population was students of Indraprasta University into two classes:1st class consisted of 20 students and the 2nd class consisted of 24 students. The data were attained by using questionnaire for communication skills, observation sheet for the implementation of TPS and SGQ cooperative learning model, and documentation for mid and final test. The result showed that (1) there was a significant effect of TPS implementation toward students’ communication skills; (2) there was a significant effect of SGQ implementation toward students’ communication skills; and (3) there was no difference of students’ communication skills between the implementation of TPS and SGQ cooperative learning model.